Extended spectrum betalactamase and Carbapenemase producing gram negative bacteria from healthcare workers gowns at Debre Berhan Comprehensive Specialized Hospital, Ethiopia - Sisay Gebrish Sharew; Daniel Gebretsadik Weldehanna; Demissew Shenkute Gebreyes; Tsegahun Asfaw Abebe; Agumas Shibabaw (Scientific Reports)
Abstract Extended-spectrum beta-lactamase (ESBL) and carbapenemase-producing (CP) gram-negative bacteria are the major public health concerns. Gowns used by healthcare workers (HCWs) in daily practice are a source of hospital-acquired infections in hospital settings. The study aimed to determine the prevalence of extended-spectrum beta-lactamase and carbapenemase-producing gram-negative bacteria from gowns of healthcare workers at Debre Berhan Comprehensive Specialized Hospital, Amhara Regional State, Ethiopia. A hospital-based cross-sectional study was conducted from August to October 2022. A total of 226 swab samples were collected from gowns of HCWs and cultured on MacConkey agar. Bacterial identifications were done by standard biochemical tests. Screening for ESBL and carbapenemase production was done using CHROME agar. Confirmation of ESBL and carbapenemase production was done by the combination disk method and modified carbapenem inactivation method, respectively. Data were analyzed by using SPSS version 25. The overall contamination rate of gowns was 46.9% (106/226). Among 226 swab samples, a total of 117 (51.7%) gram-negative bacteria were isolated. Among these, the most frequent isolates were E. coli, accounted 36 (30.8%) followed by K. pneumoniae, 26(22.2%). The overall multi-drug resistance (MDR) rate was 65 (55.6%). Of the 117 isolates, 17(14.5%) and 12(10.3%) were ESBL and carbapenemase producers respectively. Gown type (p = 0.041), laundering practice (p = 0.045), number of gowns (p = 0.002), and gown washing frequency per week (p = 0.017).were significantly associated with bacterial contamination of gowns. In this study, the prevalence of ESBL and CP Gram-negative bacteria from gowns of healthcare workers was found to be alarming. Therefore, strict infection prevention and control practices, as well as good hygienic practices, should be implemented to reduce and prevent cross-contamination and the spread of antimicrobial-resistant strains in hospital settings.